The Reality of Using Artificial Intelligence Applications in Educating Students with Disabilities in the Sultanate of Oman from the Perspective of Their Teachers - Al-Maqrashi, Khalid Saif (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the reality of using artificial intelligence (AI) applications in educating students with disabilities from the perspective of their teachers in the Sultanate of Oman. The study employed a descriptive survey methodology and used a questionnaire as the primary data collection tool, with sample consisted of 290 teachers working in the field of special education and learning difficulties in the regions of Muscat, Al Wusta, and Dhofar. The findings revealed that the use of (AI) applications for students with disabilities in Oman was at a high level. The axis related to augmented reality applications for students with disabilities ranked first, followed by virtual reality applications and intelligent education systems. Among the main challenges identified were the lack of training programs on using AI applications, which was the top barrier. the results also indicated statistically significant differences in the average responses of the study sample regarding the reality of AI application use based on the specialization variable, favoring teachers of students with learning difficulties. Additionally, significant differences were observed from the teachers' perspectives attributed to the variable of years of experience.
Keywords: Artificial Intelligence Applications; Students with Disabilities; Teachers of Students with Disabilities